The molecular immunology of complex carbohydrates-3 - Wu, Albert M. (Springer US, 2011)
Based on the proceedings of the third international symposium on Molecular Immunology of Complex Carbohydrates,? this text is the latest in a series dedicated to glycotopes, structures and functions of complex carbohydrates, recognition factors of lectins, biomolecular interactions and other glycosciences. Section I of the book pays tribute to three pioneers in the field?Walter T.J. Morgan, Elvin A. Kabat and especially Winifred M. Watkins; it presents advanced concepts concerning the structure and functions of Blood group ABH/Le-related antigens, offering a comprehensive review on human blood group ABH/Ii, Lea,b,x,y and siayl Lea,x glycotopes of human ovarian cyst glycoproteins. Section II covers the interactions of plant, bacterial and animal lectins with carbohydrates and proteins. Section III describes the structures and functions of gangliosides and microbial glycolipids. Section IV covers the physiological roles of other clycocunjugates in humans, animals, sponges and bacteria as well as aging-related alterations of glycosylation profile in humans. Section V discusses the role of carbohydrates as antigens and regulators of the immune response. Section VI addresses some aspects of the glycobiology of cancer. And section VII details new methodologies in glycol-synthesis and lectin-carbohydrate binding assays and strategies for treatment as crucial applications.